2010
DOI: 10.1152/ajpheart.00501.2009
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced senescence exaggerates postinjury neointimal formation in the old vasculature

Abstract: Vazquez-Padron RI. Stress-induced senescence exaggerates postinjury neointimal formation in the old vasculature. Am J Physiol Heart Circ Physiol 298: H66 -H74, 2010. First published October 23, 2009 doi:10.1152/ajpheart.00501.2009This study aims to demonstrate the role of stress-induced senescence in aged-related neointimal formation. We demonstrated that aging increases senescence-associated ␤-galactosidase activity (SA-␤-Gal) after vascular injury and the subsequent neointimal formation (neointima-to-media … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 44 publications
1
20
0
1
Order By: Relevance
“…Immunohistochemical analysis was performed as previously reported [13]. Briefly, 5-µ M paraffin sections were deparaffinized in xylene and rehydrated through a series of graded alcohol washes.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis was performed as previously reported [13]. Briefly, 5-µ M paraffin sections were deparaffinized in xylene and rehydrated through a series of graded alcohol washes.…”
Section: Animals and Methodsmentioning
confidence: 99%
“…33 Finally, somewhat paradoxically but potentially a result of altered cytokine expression, it has been shown that vascular smooth muscle cell senescence is associated with a 2-fold increase in neointimal formation after vascular injury. 34 Taken as a whole, our nascent knowledge of cellular senescence and telomere functionality already attests to the importance of this system in the evolution of the aging vascular phenotype, and we anticipate that the ability to therapeutically manipulate this system would represent a critical advancement in the treatment of atherothrombotic disease in the aging population.…”
Section: Telomere-telomerase Function and Atherothrombotic Diseasementioning
confidence: 99%
“…34 Considérée dans sa globalité, notre connaissance naissante de la sénescence cellulaire et de la fonction exercée par les télomères met d'ores et déjà en lumière l'importance de ce système dans l'évolution du phénotype de vieillissement vasculaire, et il ne fait aucun doute que, si nous parvenions à agir sur ce système à des fins thérapeutiques, nous accomplirions un progrès décisif dans le traitement des affections athérothrombotiques du sujet âgé.…”
unclassified
“…This proinflammatory profile suggests that senescent or senescent-like events likely occur in the central arterial wall with aging. Emerging evidence indicates that the AAASP likely delivers proinflammatory signals to exaggerate post-injury neoinima formation and enhances the arterial calcification shift with aging [2931]. …”
Section: Mediamentioning
confidence: 99%